Dispute resolution in the Islamic finance industry in Nigeria - Oseni, Umar Aimhanosi (Springer New York LLC, 2015)
With the gradual increase of Islamic finance products in Nigeria, which was spurred by the initial licenses issued to some banks by the Central Bank of Nigeria to operate Sharī‘ah-compliant banking, an unprecedented trend has been introduced in the world of Islamic finance litigation. Litigating the legality of the Islamic banking license issued by the apex bank in Nigeria was the first in the yet unknown phase of the dispute resolution trends in the nascent Islamic finance industry in the country. This study therefore examines the challenges, prospects and future directions of sustainable dispute resolution practices in the Islamic finance industry. It proposes a practical dispute resolution framework for Nigeria through best practices from three key jurisdictions—Malaysia, Indonesia and Pakistan—who have some unique mechanisms that have stood the test of time. The study concludes that for Nigeria to be able to attract foreign direct investment into its nascent Islamic finance industry, particularly from the oil rich Middle Eastern countries, it requires a sound and robust judicial system and dispute resolution mechanism that can stand the test of time.